Assessment of knowledge and attitude on breast self-examination among female college students at Adichuchanagiri University - D. R., Thanushree; B., Chandana; M., Kumaraswamy (International Journal of Research in Medical Sciences, 2024)
Background: Breast self-examination (BSE) is a preventive and easy way for people to keep an eye on the health of their breasts. People who routinely examine their breasts may be able to identify changes or abnormalities at an early stage, which may help in the early diagnosis of breast cancer. This self-care routine encourages an active approach to breast health and actively participate in their own well-being. Objectives of the study were assessment of the knowledge and attitude on breast self-examination among female college students, to assess the major barrier to perform breast self-examination, and to assess the impact of pharmacist mediated education program on breast cancer. Methods: This study is an interventional cross-sectional community based-survey. 1007 students’ female college students at Adichuchanagiri University in B. G. Nagar belonging to 18-33 years were chosen at random using stratified sampling. Knowledge, attitude on breast cancer. Data was analyzed using statistical package for the social science (SPSS) version 25. Results: In pre-test out of 1007 students 251 students had good knowledge about breast self-examination. In post-test 1006 members had good knowledge about breast self-examination. In our study statistical relation found between pre and post questionnaires (p=0.001). Conclusions: The study emphasizes how important it is to launch educational programs to increase awareness of breast self-examination. Additionally, awareness needs to be raised by removing known barriers. It is important to encourage women in the community to self-examine their breasts and to report any changes to a doctor as soon as possible.